Polypharmacy in older adults: a narrative review of definitions, epidemiology and consequences - Pazan, Farhad; Wehling, Martin (European geriatric medicine, 2021)
Background  The number of older adults has been constantly growing around the globe. Consequently, multimorbidity and related polypharmacy have become an increasing problem. In the absence of an accepted agreement on the definition of polypharmacy, data on its prevalence in various studies are not easily comparable. Besides, the evidence on the potential adverse clinical outcomes related to polypharmacy is limited though polypharmacy has been linked to numerous adverse clinical outcomes. This narrative review aims to find and summarize recent publications on definitions, epidemiology and clinical consequences of polypharmacy. - Methods  The MEDLINE database was used to identify recent publications on the definition, prevalence and clinical consequences of polypharmacy using their respective common terms and their variations. Systematic reviews and original studies published between 2015 and 2020 were included. - Results  One hundred and forty-three definitions of polypharmacy and associated terms were found. Most of them are numerical definitions. Its prevalence ranges from 4% among community-dwelling older people to over 96.5% in hospitalized patients. In addition, numerous adverse clinical outcomes were associated with polypharmacy. - Conclusion  The term polypharmacy is imprecise, and its definition is yet subject to an ongoing debate. The clinically oriented definitions of polypharmacy found in this review such as appropriate or necessary polypharmacy are more useful and relevant. Regardless of the definition, polypharmacy is highly prevalent in older adults, particularly in nursing home residents and hospitalized patients. Approaches to increase the appropriateness of polypharmacy can improve clinical outcomes in older adults.
Gesehen am 14.07.2023